Effectiveness of Public Administration Policies in Delivering Services to Citizens - Mateen, Nawaskhan; Malik, Abdul; Parwaiz, Lodis (Journal Social Civilecial, 2024)
This study considers an evaluation of how policies formulated in public administration can help enhance service delivery in Afghanistan which faces numerous political, historical, and socioeconomic issues. The study employs a method known as quantitative case study to look at the adherence of the various sectors in public administration to policies affecting education, health, and municipalities. Information was collected using structured interviews, focus group discussions, document review, and observations with participants being public sector representatives and users of public services. The study also established the fact that bureaucratic constraints, corruption, lack of resources and socio-political factors hinder successful provisioning of public services. Some challenges which came up before the public and citizens included weak institutional framework and regional disparities in the access to services. In addition, the paper demonstrates how the framework of governance institutions, political stability, and service delivers interface in the context of the post-conflict country. These results add to the current body of literature on public administration in fragile and conflict-affected states by presenting a case for the need for extensive and system reform with a focus on increasing the accountable and open state, as well as enhancing local governance systems. The findings of this study provide prescriptive implications for enhancing service provision and governance efficiency in Afghanistan and analogous states after conflict.